COMPOSICIÓN ORNITOLÓGICA DEL LITORAL DE HUANCHAQUITO, TRUJILLO, LA LIBERTAD, JUNIO – OCTUBRE 2018 - Delgado Azabache, Raizza Vanessa (2018)
In the present work the ornithological composition of the Huanchaquito coast, province of Trujillo, La Libertad, was determined, distributed in three strata: sea, intertidal and gramadal. Using Systematic Randomized Stratified Sampling, using the Point Abundance Index (IPA) with fixed points of 100 meters radius for 10 minutes and the Kilometer Index of abundance or transect in stripe (IKA) with 2.2 Km in length, with a width of 200 m (100-100) with monthly sightings. The data analysis reveals the richness, abundance and specific diversity of the coastal ornithology of the Province of Trujillo. This will allow to indicate the status of the natural systems and the quality of the habitat and if they are in good conditions. A total of 30 species were determined, included in 10 orders, 15 families and 21 genera. The families with the largest number of species were Scolopacidae (6) and Laridae (5). An average was determined for the three repetitions finding a slightly low diversity (H '= 1.75, 1.62 and 1.94 bits / individuals) with a slight high dominance (D = 0.60, 0.57 and 0.67) and a low equity index (E = 0.53). , 0.51 and 0.60 H / Max). Among the most abundant species were: Pelecanus thagus, Phalacrocorax brasilianus, Calidris alba and Actitis macularis.